Teknik Ecoprint sebagai Upaya Pemberdayaan Perempuan Kreatif dan Mandiri di Desa Bumiharjo Kecamatan Guntur Kabupaten Demak - Yaafi’ Tazkiyah; Abdurrohkman Noor; Muhammad Lutfil Hakim; Maylan Maylan; Nabila Rahmanisa; Finkiana Intan Rismama; Fitria Puji Astutik; Septya Lie Mahesti; Vadhea Cahyanda Sukma (Faculty of Engineering, Universitas Semarang, 2024)
Ecoprint is one of the promising alternative business opportunities in the fashion sector. Especially in this digital era that makes it easy for someone to do everything, one of which is promoting a fashion business on social media. The purpose of this research is to introduce Bumiharjo Village women to the utilization of nature in Bumiharjo to be utilized in opening an economic business. By utilizing natural resources in the surrounding environment, ecoprint products are products that are worth selling, have a high selling price and most importantly are environmentally friendly. This research uses an experimental method because it is a research by conducting ecoprint trials using paper bags with pounding techniques, further examining research on ecoprint techniques specifically using data collection methods Literature Study and Using Observation methods. The results showed that the ecoprint training using the pounding technique increased the creativity of the mothers compared to before the training was conducted. There are mothers who want to try to make ecoprint crafts independently. Researchers hope that this ecoprint training can be a business opportunity and empowerment of creative and independent women for the mothers of Bumiharjo Village.